Pengembangan E-Komik “Kabah” tentang Kalimat Tayyibah pada Pembelajaran PAI Kelas 4 SD - Gesela, Genny Gita; Fathurrohmah, Deliyana; Dewi, Noviasari; Aeni, Ani Nur (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the use of digital learning media, particularly e-comics, in Islamic education, which significantly impacts students' motivation and understanding. The purpose of this research is to develop and evaluate the effectiveness of the e-comic learning media KABAH (Kalimat Thayyibah) to enhance students' understanding of the thayyibah greeting phrases. This study employed a design and development (D&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, conducted at SD Negeri Mandalaherang III with the involvement of 16 students. A student assessment questionnaire and media validation instruments were used to collect data, which were then analyzed descriptively. The results indicate that the KABAH e-comic achieved a very good feasibility score of 91.25% for media expert validation and 92.5% for content expert validation. Additionally, student questionnaire results show that this e-comic is engaging and aids in understanding the material. These findings support the theory that innovative learning methods can enhance students' understanding.